PENGARUH MODEL PEMBELAJARAN CORE (Connecting, Organizing, Reflecting, Extending) TERHADAP PEMECAHAN BARIS DAN DERET MATEMATIKA - Hidayati, Nur; Sutanto, Sutanto (Jurnal Ilmiah Sains dan Teknologi, 2018)
Main purpose of the studied was carried – out on 1. Improving the academic – value on Mathematics-problem and 2. Increasing speed learning-value of Mathematics-problems through technical CORE-Model. Total experiment sample of the studied consist of 20 person pupils respectively, was apply with 1st stage to training and guidance 2nd stage was conditioning environment and 3thstage was experiment-periode, neverthelese each stage consist of 10 days. Date were analised by two-ways classification without interaction. Result of the studied informs as follows: 1. Highly significance (0,1%) difference on improving of academic-value of Matematics-problems between CORE-Model with conventional-learning technics respectively 2. Highly significance (0,1%) difference on speed-learning of Matematics-problems between CORE-Model with conventional-learning technics respectively.